Flop transitions in M-theory cosmology - Brändle, M; Lukas, A (2003)
We study flop transitions for M-theory on Calabi-Yau threefolds and their applications to cosmology in the context of the effective five-dimensional supergravity theory. In particular, the additional hypermultiplet which becomes massless at the transition is included in the effective action. We find the potential for this hypermultiplet which includes quadratic and quartic terms as well as additional dependence on the Kähler moduli. By constructing explicit cosmological solutions, it is demonstrated that a flop transition can indeed be achieved dynamically, as long as the hypermultiplet is set to zero. For an explicit example we find that once excitations of the hypermultiplet are taken into account, the transition is genetically not completed but the system is classically stabilized close to the transition region, at least as long as the transition states do not vanish. Regions of moduli space close to flop transitions can, therefore, be viewed as preferred by the cosmological evolution. ©2003 The American Physical Society.